A pre‐clinical functional assessment of an acellular scaffold intended for the treatment of hard‐to‐heal wounds. Issue 2 (5th April 2013) - Shooter, Gary K; Van Lonkhuyzen, Derek R; Croll, Tristan I; Cao, Yang; Xie, Yan; Broadbent, James A; Stupar, Dario; Lynam, Emily C; Upton, Zee
Abstract: The majority of the population experience successful wound‐healing outcomes; however, 1–3% of those aged over 65 years experience delayed wound healing and wound perpetuation. These hard‐to‐heal wounds contain degraded and dysfunctional extracellular matrix (ECM); yet, the integrity of this structure is critical in the processes of normal wound healing. Here, we evaluated a novel synthetic matrix protein for its ability to act as an acellular scaffold that could replace dysfunctional ECM. In this regard, the synthetic protein was subjected to adsorption and diffusion assays using collagen and human dermal tissues; evaluated for its ability to influence keratinocyte and fibroblast attachment, migration and proliferation and assessed for its ability to influence in vivo wound healing in a porcine model. Critically, these experiments demonstrate that the matrix protein adsorbed to collagen and human dermal tissue but did not diffuse through human dermal tissue within a 24‐hour observation period, and facilitated cell attachment, migration and proliferation. In a porcine wound‐healing model, significantly smaller wound areas were observed in the test group compared with the control group following the third treatment. These data provide evidence that the synthetic matrix protein has the ability to function as an acellular scaffold for wound‐healing purposes.